Sputum colour charts to guide antibiotic self-treatment of acute exacerbation of chronic obstructive pulmonary disease: the Colour-COPD RCT - Eleni Gkini; Rachel L Adams; Daniella Spittle; Paul Ellis; Katherine Allsopp; Sanya Saleem; Matthew McKenna; Nick le Mesurier; Nicola Gale; Sarah Tearne; Peymane Adab; Rachel E Jordan; et al. (Health Technology Assessment, 2025)
Background Chronic obstructive pulmonary disease exacerbations (acute exacerbation of chronic obstructive pulmonary disease) are characterised by increased sputum volume, purulence and breathlessness. Patients are encouraged to recognise and treat acute exacerbation of chronic obstructive pulmonary disease as part of a self-management plan. Only half of acute exacerbation of chronic obstructive pulmonary disease are caused by bacterial infection, but self-management plans generally advocate use of antibiotics and steroids for all events, hence antibiotics may be overused. Sputum colour relates closely to bacterial load; thus it could determine whether antibiotics are appropriate. This pragmatic randomised controlled trial tested whether use of a sputum colour chart is safe and effective in United Kingdom primary care. Methods Colour chronic obstructive pulmonary disease was a multicentre, randomised controlled trial in adults with chronic obstructive pulmonary disease who had ≥ 2 acute exacerbations of chronic obstructive pulmonary disease or ≥ 1 hospital admission for acute exacerbation of chronic obstructive pulmonary disease in the preceding year. The primary objective was to demonstrate that the Bronkotest® (London) sputum colour chart is non-inferior to usual care (safe). The primary outcome was rate of hospital admission for acute exacerbation of chronic obstructive pulmonary disease at 12 months; secondary outcomes included requirement for second courses of treatment and quality of life (chronic obstructive pulmonary disease assessment test score). Nested substudies examining daily symptoms via an e-diary and sputum culture assessed untreated acute exacerbation of chronic obstructive pulmonary disease rate and antibiotic resistance, respectively. A process evaluation examined trial fidelity and acceptability of the intervention, employing qualitative research methods incorporating patients as co-researchers. Limitations The study was terminated early due to low recruitment (115/2954 planned sample size). Results One hundred and fifteen patients were recruited and randomised 1 : 1 to colour chart use or usual care; they generally had severe Global Initiative for Chronic Obstructive Lung Disease D chronic obstructive pulmonary disease, with significant breathlessness (54% Medical Research Council score of 4 or 5) and poor quality of life (chronic obstructive pulmonary disease assessment test score at baseline 24). Comorbid respiratory and systemic disease was common. Self-management was delivered well in both arms, and the colour chart acceptable to patients and staff; no specific issues for patients with multiple long-term conditions were identified. Hospital admissions for acute exacerbation of chronic obstructive pulmonary disease tended to occur more in colour chart users [32 vs. 16%, relative risk 1.95 (0.92 to 4.18)], and antibiotic courses within 14 days of initial acute exacerbation of chronic obstructive pulmonary disease treatment were also more common [34 vs. 18%, adjusted relative risk 1.80 (0.85 to 3.79)]. Despite this, quality of life was better in colour chart users at 12 months [chronic obstructive pulmonary disease assessment test 19.9 vs. −24.5, adjusted mean difference −2.95 (−5.93 to −0.04)]. Thirty-eight patients consented to the sputum substudy, and 57 samples were received (42 stable state, 15 during acute exacerbation of chronic obstructive pulmonary disease), of which 30% contained a potentially pathogenic bacterium. Sputum was more likely to be purulent in subjects with bronchiectasis, independent of disease state (stable vs. exacerbation) or whether the sample was positive for a potentially pathogenic bacterium, suggesting that colour alone cannot be used to guide antibiotic use. Eleven patients completed the e-diary study, and 42 symptom-defined acute exacerbation of chronic obstructive pulmonary disease events were captured, many of which were untreated, exhibiting lower EXAcerbations of Chronic Pulmonary Disease Tool scores than those which were treated. Untreated events were slower to settle. Differences between study arms were not meaningful to compute due to low numbers. Conclusion and future work Our results imply that the Bronkotest sputum colour chart is unlikely to be a useful addition to self-management for chronic obstructive pulmonary disease patients in primary care, but further work is required to confirm this. Funding This synopsis presents independent research funded by the National Institute for Health and Care Research (NIHR) Health Technology Assessment programme as award number 17/128/04. Plain language summary Chronic obstructive pulmonary disease causes breathlessness, impairs quality of life and leads to flare-ups, known as exacerbations, which patients are taught to treat using a self-management plan and ‘rescue pack’ of antibiotics and steroids. However, since only half of the exacerbations are caused by bacteria, antibiotics might be overused. The Colour chronic obstructive pulmonary disease trial was a multicentre study which randomly allocated 115 adults with chronic obstructive pulmonary disease who had experienced two or more exacerbations in the preceding year to use of a sputum colour chart (Bronkotest®) alongside their self-management plan, or to usual care. Patients were seen at baseline and 12 months later. We also interviewed patients and healthcare staff to find out if using a colour chart would be acceptable. Some patients sent sputum samples to us, and some patients recorded symptoms daily using an electronic diary (e-diary). We intended to recruit 2954 people, but the study stopped early because of recruitment difficulties. Patients generally had severe chronic obstructive pulmonary disease, were breathless on walking short distances and had poor quality of life. Self-management was delivered well, and the colour chart was easy to use and acceptable to patients and staff. Hospital admissions for exacerbations occurred more in colour chart users (32% vs. 16%), and antibiotic courses within 14 days of initial exacerbation treatment were also more common (34% vs. 18%). However, patients felt better if they were using a colour chart. Sputum colour did not relate to whether the sample had bacteria in it. Eleven patients completed the e-diary study, and 42 symptom-defined exacerbations happened, many of which were untreated and slower to settle. Since hospital admissions were more common, and sputum colour did not identify bacteria reliably, the Bronkotest sputum colour chart is unlikely to help chronic obstructive pulmonary disease self-management, but further research is needed because of the low recruitment numbers.